Effect of dry dynamic apnea on aerobic power in elite rugby athletes: a warm-up method - Wendi, Wang; Dongzhe, Wu; Hao, Wang; Yongjin, Shi; Xiaolin, Gao (Frontiers in Physiology, 2024)
While long-term dynamic breath-holding training has been extensively studied to enhance cardiopulmonary function in athletes, limited research has explored the impact of a single breath-holding session on subsequent athletic capacity. In addition, Dry Dynamic Apnea (DA) has a more immediate physiological response than wet and static breath-holding. This study aims to assess the immediate effects of a single session of DA on the aerobic power and hematological parameters of elite athletes.Seventeen elite male rugby athletes (average age 23.5±1.8) participated in this study. Two warm-up protocols were employed prior to incremental exercise: a standard warm-up (10 minutes of no-load pedaling) and a DA warm-up (10 minutes of no-load pedaling accompanied by six maximum capacity breath holds, with 30 seconds between each breath hold). Fingertip blood indicators were measured before and after warm-up. The incremental exercise test assessed aerobic parameters with self-regulation applied throughout the study.Compared to the baseline warm-up, the DA warm-up resulted in a significant increase in VO2peak from 3.14 to 3.38 L/min (7.64% change, P<0.05). HRmax increased from 170 to 183 bpm (7.34% change, P<0.05), and HRpeak increased from 169 to 182 bpm (7.52% change, P<0.05). Hematocrit and hemoglobin showed differential changes between the two warm-up methods(PHematocrit=0.674；Phemoglobin=0.707).This study investigates how DA influences physiological factors such as spleen contraction, oxygen uptake, and sympathetic nerve activation compared to traditional warm-up methods. Immediate improvements in aerobic power suggest reduced vagus nerve stimulation, heightened sympathetic activity, and alterations in respiratory metabolism induced by the voluntarily hypoxia-triggered warm-up. Further research is warranted to comprehensively understand these physiological responses and optimize warm-up strategies for elite athletic performance.